Does Hallux Valgus Correction Reduce the Width of the Forefoot?. Issue 2 (April 2020) - Panchbhavi, Vinod; Cordova, Justin; Chen, Jie; Janney, Cory
Background: Hallux valgus has been associated with a widened forefoot. Most surgical procedures for the correction of hallux valgus have the potential to reduce forefoot width. Success after hallux valgus surgery is correlated with relief of toe pain in conventional shoes and improvement in the appearance of the foot. Therefore, reduction in forefoot width, referred to as metatarsal span (MS), likely correlates with both criteria and may be a reliable radiographic indicator of success after hallux valgus surgery. Methods: Preoperative and postoperative radiographs of 52 patients who underwent correction of hallux valgus with a distal Chevron osteotomy and Akin osteotomy were evaluated by 4 observers. The observers measured the hallux valgus angle (HVA), the intermetatarsal first and second angle (IMA), and the MS. Results: Preoperative HVA ranged from 14° to 48°, IMA ranged from 6° to 25°, and MS ranged from 74.2 to 110.6 mm. The average HVA improvement was 19.4°, IMA improvement was 6.7°, and MS reduction was 8.7 mm. No correlation was identified with regard to correction of the HVA or IMA to MS. Conclusion: Digital radiographic linear measurements were easily and reliably made. Therefore, linear measurements as described in this article can be used as a tool to evaluate if clinical outcomes correlate with reduction of MS. A distal Chevron with an Akin osteotomy has the potential to reduce forefoot width. Levels of Evidence: Level IV: Case series